Tinjauan Aktifitas Pasar Tradisional Yang Dipergunakan Masyarakat Dalam Mempengaruhi Kinerja Jalan (Studi Kasus: Pasar Teratai Pontianak) - Ranty Christiana; Ika Muthya Anggraini; Hezliana Syahwanti (Jurnal Serambi Engineering, 2021)
The number of people utilizing the city market facility is likely to increase day by day. It causes  the market conditions to become congested. Therefore, it cannot be denied that  the  existing main roads are definetly affected by this condition. For this reason, the performance of the roads needs to be further reviewed since they are openly accessed by the community also due tothe influence of Teratai Market activities. A descriptive method is used in this studyby surveying the conditions of the Komyos Sudarso road. The calculation  is carried out based on the Indonesian Road Capacity Manual (MKJI) 1997. The results of this study shows that the activities of the Teratai Market greatly affect road capacity resulting in the increased of traffic volume. When the market operates, the trafficbecomes denser as  such a large number of vehicles are commuting on the road. The observation area is included in a commercial area with high roadside activity as evidenced by a side friction survey which shows a high side friction class count with a weighted frequency of 508.3. The results of the road performance show that Jalan Komyos Sudarso is still not saturated, in which the DS value is 0.34 and the average speed of light vehicles is 42 km/hour.